Dermal Capillary Clearance: Physiology and Modeling - Kretsos, K.; Kasting, G.B. (Skin pharmacology and physiology, 2005)
Substances applied to the skin surface may permeate deeper tissue layers and pass into the body’s systemic circulation by entering blood or lymphatic vessels in the dermis. The purpose of this review is an in-depth analysis of the dermal clearance/exchange process and its constituents: transport through the interstitium, permeability of the microvascular barrier and removal via the circulation. We adapt an ‘engineering’ viewpoint with emphasis on quantifying the dermal microcirculatory physiology, providing the theoretical framework for the physics of key transport processes and reviewing the available computational clearance models in a comparative manner. Selected experimental data which may serve as valuable input to modeling attempts are also reported.